Optimization of MBR hydrodynamics for cake layer fouling control through CFD simulation and RSM design. (March 2017) - Yang, Min; Yu, Dawei; Liu, Mengmeng; Zheng, Libing; Zheng, Xiang; Wei, Yuansong; Wang, Fang; Fan, Yaobo
Graphical abstract: Highlights: CFD model and RSM design was developed for mitigation of cake layer fouling in MBR. Sludge concentration was the most decisive for shear stress and particle deposition. MLSS of 8820 mg L −1 was optimal for the reduction of reversible membrane fouling. Bubble diameter was more decisive than air flowrate for membrane shear stress. Abstract: Membrane fouling is an important issue for membrane bioreactor (MBR) operation. This paper aims at the investigation and the controlling of reversible membrane fouling due to cake layer formation and foulants deposition by optimizing MBR hydrodynamics through the combination of computational fluid dynamics (CFD) and design of experiment (DOE). The model was validated by comparing simulations with measurements of liquid velocity and dissolved oxygen (DO) concentration in a lab-scale submerged MBR. The results demonstrated that the sludge concentration is the most influencing for responses including shear stress, particle deposition propensity (PDP), sludge viscosity and strain rate. A medium sludge concentration of 8820 mg L −1 is optimal for the reduction of reversible fouling in this submerged MBR. The bubble diameter is more decisive than air flowrate for membrane shear stress due to its role in sludge viscosity. The optimal bubble diameter was at around 4.8 mm for both of shear stress and PDP.